Reinventing state capitalism : Leviathan in business, Brazil and beyond - Musacchio, Aldo; Lazzarini, Sérgio G. (Harvard University Press, 2014)
The wave of liberalization that swept world markets in the 1980s and 90s altered the ways that governments manage their economies. Reinventing State Capitalism analyzes the rise of new species of state capitalism in which governments interact with private investors either as majority or minority shareholders in publicly-traded corporations or as financial backers of purely private firms (the so-called "national champions")